Predictors of well-being in cancer survivors - Pais-Ribeiro, José Luís (2015)
Nearly 65% of adults diagnosed with cancer will live, at least, five years after the diagnostic. If the treatment is lengthy and disruptive, the persons can experience difficulties in returning to normal daily life. Research shows that cancer survivors suffer from more psychological distress than those who have never experienced cancer (5.6% versus 3.0%), reason why psychoeducational programs are necessary to help people return to everyday life. The objective of the present study is to identify psychosocial predictors of well being in people that survive cancer, are in stable condition, and a diagnosis of longer than three years.